2015
DOI: 10.1017/thg.2015.73
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Scan of DNA Methylation Markers for Distinguishing Monozygotic Twins

Abstract: Identification of individuals within pairs of monozygotic (MZ) twins remains unresolved using common forensic DNA typing technology. For some criminal cases involving MZ twins as suspects, the twins had to be released due to inability to identify which of the pair was the perpetrator. In this study, we performed a genome-wide scan on whole blood-derived DNA from four pairs of healthy phenotypically concordant MZ twins using the methylated DNA immunoprecipitation sequencing technology to identify candidate DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…We investigated whether tDMSs appear more often in specific chromosomal regions according to CpG content, and observed that 27% of tDMSs are annotated to fall in CGIs, 25% in CGI shores, 6% in CGI shelves and 42% are non-CGI probes [ Figure S3D]. At this cutoff, it seems that CGI probes are highly represented, which has been previously supported by similar studies [25,28]. 20…”
Section: Identification Of Candidate Tdmss In Reference-type Dnasupporting
confidence: 71%
See 2 more Smart Citations
“…We investigated whether tDMSs appear more often in specific chromosomal regions according to CpG content, and observed that 27% of tDMSs are annotated to fall in CGIs, 25% in CGI shores, 6% in CGI shelves and 42% are non-CGI probes [ Figure S3D]. At this cutoff, it seems that CGI probes are highly represented, which has been previously supported by similar studies [25,28]. 20…”
Section: Identification Of Candidate Tdmss In Reference-type Dnasupporting
confidence: 71%
“…Although the extent of these differences, and to what degree they are shared by different MZ twin pairs, is yet not understood, the potential of using DNA methylation to distinguish between MZ twins for forensic purposes has already been recognized [23][24][25][26][27][28], albeit via limited studies. In an initial study, Li et al tested blood DNA samples of 22 adult MZ twin pairs by using the Illumina Infinium Human Methylation 27K BeadChip array that allows for the co-analysis of 27,578 CpG sites, which revealed significant DNA methylation differences (377 CpG sites, methylation difference >0.17) [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically identical MZ twins are sometimes discordant for certain phenotypes [ 61 ], indicating epigenetic involvement [ 6 ], and several studies have demonstrated that there is considerable epigenetic variation within MZ twin pairs. Although some studies have explored the value of epigenetic profiling in forensically discriminating MZ twins [ 62 , 63 ], it is not yet fully established whether the observed twin-to-twin differences are twin pair-specific, or might be universal and applicable across twin pairs, as would be preferred. Recently, a first attempt was made to demonstrate the feasibility of differentiating between MZ twins using forensic epigenetics [ 15 ].…”
Section: Current Progress In Forensic Epigeneticsmentioning
confidence: 99%
“…Observed epigenetic drifts within MZ twin pairs can be seen not only at specific genomic loci [ 15 , 16 ], but also at a global level [ 12 ], which has unraveled epigenetics’ role in development, ageing, and disease [ 17 , 18 , 19 , 20 , 21 , 22 ]. The potential of DNA methylation profiling for the discrimination between MZ twins in the forensic setting has already been proposed [ 23 , 24 , 25 , 26 , 27 , 28 ]; however, these previous studies mainly included reference-type DNA such as whole blood or buccal swabs. Investigations were not extended to trace-type DNA such as from blood or saliva stains, while combining both parts is needed in the forensic setting.…”
Section: Introductionmentioning
confidence: 99%